2016
DOI: 10.1002/2211-5463.12000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Src homology 2 domain‐containing phosphatase 1 increases insulin sensitivity in high‐fat diet‐induced insulin‐resistant mice

Abstract: Insulin resistance plays a crucial role in the development of type 2 diabetes. Insulin receptor signalling is antagonized and tightly controlled by protein tyrosine phosphatases (PTPs). However, the precise role of the PTP src homology 2 domain‐containing phosphatase 1 (SHP‐1) in insulin resistance has not been explored. Male C57BL/6J mice were fed a high‐fat diet (HFD, 60% kcal from fat), to induce insulin resistance, or a low‐fat diet (LFD, 10% kcal from fat) for 10 weeks. Afterwards, HFD‐fed mice were pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Sodium stibogluconate, a specific SHP-1 inhibitor 24 , were administered daily (20 mg/kg/day by intraperitoneal injection) in the CCl 4 model for 2 weeks and in the BDL model for 1 week to investigate the effect of SHP-1 inhibition on fibrogenesis. All experimental animal procedures were in accordance with protocols approved by the Institutional Laboratory Animal Care and Use Committee of National Taiwan University.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium stibogluconate, a specific SHP-1 inhibitor 24 , were administered daily (20 mg/kg/day by intraperitoneal injection) in the CCl 4 model for 2 weeks and in the BDL model for 1 week to investigate the effect of SHP-1 inhibition on fibrogenesis. All experimental animal procedures were in accordance with protocols approved by the Institutional Laboratory Animal Care and Use Committee of National Taiwan University.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from genetic deletion, the pharmacological inhibition of SHP-1 using sodium stibogluconate, a known inhibitor of SHP-1, was efficient in ameliorating the metabolic phenotype in a mouse model of high-fat-diet (HFD)-induced insulin resistance 12 . Additionally, the anti-hyperglycemic and anti-inflammatory actions of metformin in an obese insulin-resistant mouse model were found to be associated with reduced SHP-1 expression and activity in AT 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As expected, HFD time-dependently induced obesity, changes in body composition, and reduced glucose tolerance and insulin sensitivity [3840]. Clinical observations have shown that diabetics have a higher risk for development and prevalence of PAH [10, 14, 41], with the causal and underlying mechanism yet to be established.…”
Section: Discussionmentioning
confidence: 76%